2002
DOI: 10.1105/tpc.001586
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Protein Transport between the Endoplasmic Reticulum and the Golgi in Tobacco Leaves Is Energy Dependent but Cytoskeleton Independent

Abstract: The mechanisms that control protein transport between the endoplasmic reticulum (ER) and the Golgi apparatus are poorly characterized in plants. Here, we examine in tobacco leaves the structural relationship between Golgi and ER membranes using electron microscopy and demonstrate that Golgi membranes contain elements that are in close association and/or in direct contact with the ER. We further visualized protein trafficking between the ER and the Golgi using Golgi marker proteins tagged with green fluorescent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
378
0
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 296 publications
(397 citation statements)
references
References 62 publications
16
378
0
3
Order By: Relevance
“…Collectively, these findings are consistent with the proposal that the intracellular transport of TMV occurs via the ER and that the adjacent actin cytoskeleton may exert control over ER-mediated transport via myosin bridges. The observation that transient ABD2:GFP expression interfered with myosin-mediated motility is in agreement with several other reports indicating that the expression of GFP fusions with actin-binding proteins can interfere with actin dynamics and organization, even though they are valuable tools for evaluating cytoskeletal functions (Kost et al, 1998;Mathur et al, 1999;Fu et al, 2001;Brandizzi et al, 2002;Ilgenfritz et al, 2003;Holweg et al, 2004;Ketelaar et al, 2004;Weerasinghe et al, 2005;Xu and Scheres, 2005;Holweg, 2007;Wang et al, 2008). The inhibition of myosin-based dynamics upon transient expression of ABD2:GFP in our N. benthamiana system is probably related to the ABD2:GFP expression level, which during the time of the experiment (1.5 and 2.5 dpa) was in excess of the level of ABD2:GFP in transgenic plants.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Collectively, these findings are consistent with the proposal that the intracellular transport of TMV occurs via the ER and that the adjacent actin cytoskeleton may exert control over ER-mediated transport via myosin bridges. The observation that transient ABD2:GFP expression interfered with myosin-mediated motility is in agreement with several other reports indicating that the expression of GFP fusions with actin-binding proteins can interfere with actin dynamics and organization, even though they are valuable tools for evaluating cytoskeletal functions (Kost et al, 1998;Mathur et al, 1999;Fu et al, 2001;Brandizzi et al, 2002;Ilgenfritz et al, 2003;Holweg et al, 2004;Ketelaar et al, 2004;Weerasinghe et al, 2005;Xu and Scheres, 2005;Holweg, 2007;Wang et al, 2008). The inhibition of myosin-based dynamics upon transient expression of ABD2:GFP in our N. benthamiana system is probably related to the ABD2:GFP expression level, which during the time of the experiment (1.5 and 2.5 dpa) was in excess of the level of ABD2:GFP in transgenic plants.…”
Section: Discussionsupporting
confidence: 78%
“…2C) and is highly dynamic. A dynamic ER network was also revealed by time-lapse analysis of wildtype plants in which the ER was labeled by transient expression of GFP:HDEL, RFP:HDEL, or TM17:GFP, an ER transmembrane peptide fused to GFP (Brandizzi et al, 2002; data not shown). Transient expression of RFP:HDEL in ABD2:GFP transgenic plants revealed that transgenic ABD2:GFP expression does not interfere with the structure and dynamic movements of the ER (Fig.…”
Section: Labeling Of Actin Filaments With Abd:gfpmentioning
confidence: 99%
See 1 more Smart Citation
“…It probably works with the COPII machinery but a COPII independent pathway is also possible [49]. Surprisingly, the transfer from ER to Golgi is independent of actin or microtubules [50]. The long-standing contact between the reticulum and the Golgi is apparently sufficient to support the transfer.…”
Section: Reticulum and Golgi Exchangesmentioning
confidence: 99%
“…Graphs were prepared with KaleidaGraph (Synergy Software, Reading, PA). The mobile fraction was calculated as follows (Ellenberg et al, 1997;Brandizzi et al, 2002) …”
mentioning
confidence: 99%